Study of grain growth during austenitisation of a pearlitic steel with two starting conditions. (7th February 2018) - Bhattacharya, B.; Bhattacharyya, T.; Haldar, A.
Abstract : A pearlitic steel was subjected to isothermal austenitisation treatments at various temperatures and time lengths at each temperature. The steel was under two different starting conditions, namely, cast + forged condition and wire rod condition with 8 mm diameter. For the two different starting conditions, there was a significant difference in grain growth kinetics and activation energy values. Also, there was a significant drop of activation energy value at higher temperature range. The activation energy values were determined to be 161 and 108 kJ mol −1, respectively, for the temperature ranges 850–950 and 950–1050°C, in case of cast + forged sample and these were 225 and 170 kJ mol −1, respectively, for the fully processed rod sample. Self-diffusion and grain boundary diffusion were the most likely processes that governed the austenite grain growth.